ANALISIS HUKUM TERHADAP PENYAMPAIAN INFORMASI YANG MNEYESATKAN YANG MENGAKIBATKAN KERUGIAN KONSUMEN DALAM TRANSAKSI ELEKTRONIK (Studi Kasus Putusan No.650/Pid.Sus/PN Mks): LEGAL ANALYSIS OF THE SUBMISSION OF MISLEADING INFORMATION THAT CAUSES CONSUMER LOSS IN ELECTRONIC TRANSACTIONS (Case Study of Decision No.650/Pid.Sus/PN Mks) - Iksan Ariyanto; Mas, Marwan; Hamid, Abd. Haris (Faculty Of Law Bosowa University, 2021)
This study aims to determine: 1) The application of criminal sanctions against the delivery of misleading information that results in consumer losses in electronic transactions in criminal case number 650/Pid.Sus./2020/PN.Mks; 2) The judge's legal considerations in imposing a criminal decision on the delivery of misleading information that results in consumer losses in electronic transactions in decision number 650/Pid.Sus/2020/PN.Mks The research method of the research is descriptive qualitative research by conducting interviews with related parties who handle these cases. The results of the study shows that: 1) The application of criminal sanctions against the delivery of misleading information that results in consumer losses in electronic transactions in the decision of case number 650/Pid.Sus/2020/PN.Mks has not shown a sense of justice for consumers (victims), because it only uses one statutory provision. 2) The judge's legal considerations in imposing a criminal decision on the delivery of misleading information that results in consumer losses in electronic transactions in decision number 650/Pid.Sus/2020/PN.Mks,